Desain e-didaktis Aljabar untuk Mengatasi Learning Obstacle Siswa MTs - Meika, Ika; Mulyanah, Mulyanah; Sartika, Nenden Suciyati; Sujana, Asep (SJME (Supremum Journal of Mathematics Education), 2025)
This study aims to determine the impact of the e-didactical design of algebra material adapted to the learning barriers experienced by Madrasah Tsanawiyah (MTs) students. This research was conducted using a qualitative method with a Didactial Design Research (DDR) approach involving three stages, namely: didactical situation analysis before learning, metapedidactic, and retrospective. The research was conducted at MTs Mathla'ul Anwar Baros, Banten with the research subjects being class VII students consisting of twelve students. The results of the preliminary study show that MTs students experience barriers to learning mathematics, indicated by the existence of several difficulties, namely difficulties in algebraic operations, difficulty in solving problems that require the application of mathematical concepts, difficulty solving story problems, and operating multiplication and division. The solution to overcome these learning barriers requires e-didactic design in the form of teaching materials that contain daily problems based on these student learning barriers. The results showed that the e-didactical design given can overcome the learning barriers of MTs students, where the results of the competency test show that the learning barriers experienced by students can be minimized, this is indicated by the average value of student learning outcomes of 96.67% and a standard deviation of 8.5.